Dampak Kebijakan Tenaga Kerja terhadap Pertumbuhan Ekonomi Indonesia di Era Desentralisasi Fiskal - Gatot Subroto (Jurnal Pendidikan dan Kebudayaan, 2014)
The purpose of this study to examine the relationship between the development of the labor market and economic performance in Indonesia. Using the time series data 1977-2010 compiled from the data available in the Indonesian Human Development Report. Models are arranged in 8 structural equation, further analysis of empirical studies using the software program SAS/ETS version 9.01 with the 2SLS method (two stage least squares) through SIMLIN procedures that provide support that here has a two-way relationship between the development of the labor market and national economic performance. Besides, describing the factors that influence the development of economic growth seen from the labor market and fiscal, as well as analyzing the impact of alternative employment and fiscal policies that affect economic growth. The benefits of this study are expected to constitute a material consideration government decisionmakers and local government as the implementation of regional autonomy within the framework of the national economy and the sector as a balance between regions. As a result, national output average wages, inflation, unemployment and the lag has a positive influence on the level of unemployment, and the unemployment rate, the total government revenue, and the lag of government spending on education and health has a positive influence on the education sector and government spending health. ABSTRAKTujuan studi ini untuk mengkaji hubungan antara pembangunan pasar tenaga kerja dan kinerja ekonomi di Indonesia. Menggunakan data time series tahun 1977-2010 disusun dari data yang tersedia dalam Indonesian Human Development Report. Model disusun dalam 8 persamaan struktural, selanjutnya analisis empiris studi menggunakan program software SAS/ETS versi 9.01 dengan metode 2 SLS (two stage least squares) melalui prosedur SIMLIN yang memberikan dukungan bahwa terdapat hubungan dua arah antara pembangunan pasar tenaga kerja dan kinerja ekonomi nasional. Di samping untuk mendeskripsikan faktor-faktor pembangunan yang mempengaruhi pertumbuhan ekonomi dilihat dari pasar tenaga kerja dan fiskal, studi ini juga menganalisis dampak alternatif kebijakan tenaga kerja dan fiskal yang mempengaruhi pertumbuhan ekonomi. Manfaat studi ini diharapkan merupakan bahan pertimbangan para pengambil keputusan Pemerintah dan pemerintah daerah sebagai pelaksanaan otonomi daerah dalam kerangka perekonomian nasional dan sektoral sebagai keseimbangan antardaerah. Hasilnya, output nasional, upah rata-rata, inflasi, dan lag pengangguran mempunyai pengaruh yang positif terhadap tingkat penggangguran, serta penerimaan pemerintah total, dan lag pengeluaran pemerintah sektor pendidikan dan kesehatan mempunyai pengaruh yang positif terhadap pengeluaran pemerintah sektor pendidikan dan kesehatan.